2018
DOI: 10.1002/acn3.547
|View full text |Cite
|
Sign up to set email alerts
|

Seronegative antibody‐mediated neurology after immune checkpoint inhibitors

Abstract: Checkpoint inhibitor medications have revolutionized oncology practice, but frequently induce immune‐related adverse events. During autoimmune neurology practice over 20 months, we prospectively identified four patients with likely antibody‐mediated neurological diseases after checkpoint inhibitors: longitudinally extensive transverse myelitis, Guillain–Barré syndrome, and myasthenia gravis. All patients shared three characteristics: symptoms commenced 4 weeks after drug administration, responses to convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 20 publications
(21 reference statements)
1
51
0
Order By: Relevance
“…7 23-25 Seronegative antibody-mediated irAEs have also been described with ICIs. Wilson et al reported novel IgG and IgM reacting to relevant tissue preparations in a patient with seronegative transverse myelitis secondary to pembrolizumab and another with seronegative myasthenia gravis due to ipilimumab-nivolumab administration, 26 suggesting that ICIs uncover previously unrecognized autoreactive antibodies. This is corroborated by Gowen et al, demonstrating that patients who later developed severe irAEs to ICIs possessed a distinct pretreatment antibody pattern extending beyond the known autoantibodies, such as antinuclear, antismooth muscle, and antithyroid antibodies.…”
Section: Case Presentationmentioning
confidence: 99%
“…7 23-25 Seronegative antibody-mediated irAEs have also been described with ICIs. Wilson et al reported novel IgG and IgM reacting to relevant tissue preparations in a patient with seronegative transverse myelitis secondary to pembrolizumab and another with seronegative myasthenia gravis due to ipilimumab-nivolumab administration, 26 suggesting that ICIs uncover previously unrecognized autoreactive antibodies. This is corroborated by Gowen et al, demonstrating that patients who later developed severe irAEs to ICIs possessed a distinct pretreatment antibody pattern extending beyond the known autoantibodies, such as antinuclear, antismooth muscle, and antithyroid antibodies.…”
Section: Case Presentationmentioning
confidence: 99%
“…32,80 Myelitis, including longitudinally extensive myelitis, has also been described, and immunotherapeutic responses can be favorable. 81,82 Peripheral nerve involvement has been reported in less than 3% of patients receiving checkpoint inhibitor therapy for cancer. 83 In some patients, manifestations have been compatible with demyelinating polyradiculoneuropathies (Guillain-Barré syndrome and chronic inflammatory demyelinating polyradiculoneuropathy).…”
Section: Autoimmune Neurologic Disorders In the Era Of Checkpoint Inhmentioning
confidence: 99%
“…While detecting the autoantibodies can help to characterise the disorder, there have been reported cases of immune checkpoint inhibitor-related autoimmune encephalitis without detected autoantibody. In such cases it is the recognition of the clinical syndrome, its chronological association with therapy, and supportive imaging and CSF findings that enable a diagnosis 12…”
Section: Discussionmentioning
confidence: 99%